Analisis Implementasi dan Peningkatan Proses Bisnis Pemesanan Toko Gift Shop ABC - Rizqiyatul Khoiriyah; Aan Jelli Priana (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
ABC Gift Shop provides ordering and purchasing of souvenirs for weddings, birthdays, graduations, and other events. So far, customers are served through online orders via Instagram and offline orders that come directly to the store location. This study aims to look at the implementation of ongoing business processes and see how far the results of the evaluation can identify opportunities for improvement and recommendations for improving ABC Shop's business processes. The research method uses descriptive qualitative through interviews with informants and observations of online and offline ordering services at ABC Stores. The results of the study show that there are deficiencies in the online ordering process, such as online ordering data that is entered manually and recapitulated so that the queue process and order completion take a long time and the queues can even be swapped. Opportunities for improvement and recommendations for improvement, in this case, are being able to improve existing business processes and providing an information system for ordering souvenirs that is more flexible than social media Instagram and according to the needs of Toko ABC..